DISTRIBUTION OF SOLUTE NEAR THE ALPHA PLATES FORMED IN TITANIUM BINARY ALLOYS - Mujahid, S. A. (The Nucleus, 2020)
The partitioning of solute from Î± plates formed in Ti-5.1at.%Fe, Ti-5.4at.%V and Ti-2.6at.%Fe alloys has been investigated theoretically. These plates grow isothermally from solid solution in titanium binary alloys. The idea was to clarify whether they grow without diffusion or whether the partitioning of solute occurs after transformation. To check whether the latter mechanism is plausible, calculations have been conducted of the diffusion profile of solute and of the time required for the plate to achieve its equilibrium composition. The model based on a finite difference (FD) technique was used for the calculations. The results have been compared with the published experimental data and with that obtained using analytical technique.